Design and characterization of ceramic hollow fiber membrane derived from waste ash using phase inversion-based extrusion/sintering technique for water filtration. Issue 1 (2nd January 2021) - Tai, Zhong Sheng; Hafiz Dzarfan Othman, Mohd; Mustafa, Azeman; Mohamed Dzahir, Mohd Irfan Hatim; Hubadillah, Siti Khadijah; Koo, Khong Nee; Azali, Mohd Ariff; Alias, Nur Hashimah; Seng Ooi, Boon; Kurniawan, Tonni Agustiono; Ismail, Ahmad Fauzi
ABSTRACT: Low-cost green ceramic hollow fiber membranes (CHFM) were successfully designed and fabricated from the industrial waste ash, palm oil fuel ash (POFA) via phase inversion-based extrusion/sintering techniques for water filtration application. The extrusion process parameters such as suspension viscosity, air gap distance, and bore fluid flow rate were systematically explored to produce the membrane with desired morphology. A high suspension viscosity would result in a small macro-voids structure. Moreover, a high air gap distance would induce fiber with long macro-voids structure, while a low bore fluid flow rate would lead to the formation of distorted lumen structure. The effect of sintering temperature toward CHFM was also studied and characterized. An increase in the sintering temperature improved the membrane bending strength, but also afflicted the flux performance due to lower porosity and higher tortuosity. The developed membranes achieved excellent bending strengths of >75 MPa at lower sintering temperatures than the alternative ceramic counterparts, due to the formation of the eutectic liquid during sintering. The relatively low sintering temperature of POFA-derived CHFMs could reduce the energy consumption and sintering duration, which could be more economically attractive than their ceramic counterparts, thus benefiting industrial users.